การรับรู้ทัศนคติ และประสบการณ์การใช้เทคนิควิธีการสอนด้วยแนวคิด “การเรียนรู้เชิงรุก” ตามมุมมองของอาจารย์ผู้สอน ในรายวิชาปฏิบัติการพยาบาลอนามัยชุมชน - เพิงมาก ผจงศิลป์; เทพญา เทวิกา; ศักดิ์สองเมือง พิมพิศา; พานทอง อุดม (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2018)
บทคัดย่อ การวิจัยเพื่อพัฒนาการเรียนการสอนสาขาการพยาบาลด้วยแนวคิด“การเรียนรู้เชิงรุก” ในมุมมองของอาจารย์ผู้สอนซึ่งเป็นประสบการณ์“ใหม่”ต่อการใช้แนวคิดนี้ยังมีรายงานไว้น้อยมาก การวิจัยนำร่องนี้เพื่อศึกษาการรับรู้ทัศนคติและประสบการณ์การใช้เทคนิคและวิธีการสอนต่างๆ ของผู้สอนด้วยแนวคิด “การเรียนรู้เชิงรุก” รวมถึงสิ่งสนับสนุนหรือปัญหาอุปสรรคต่อการใช้เทคนิคและวิธีการสอนต่างๆ ผู้ให้ข้อมูลเป็นอาจารย์ประจำของภาควิชาที่สนใจและยินดีให้ข้อมูล ได้ทำการสอนหรือคุมฝึกภาคปฏิบัติ ในรายวิชาปฏิบัติการพยาบาลอนามัยชุมชน ในช่วง 1 - 2 ปีที่ผ่านมา ใช้วิธีการวิจัยเชิงคุณภาพ เก็บรวบรวมข้อมูลด้วยการสัมภาษณ์เชิงลึก (รายบุคคล) จากอาจารย์ผู้สอน (6 คน) โดยใช้ 1) ร่างแนวคำถามในประเด็นที่เกี่ยวข้อง 2) การสังเกตอย่างมีส่วนร่วมในขณะคุมฝึกปฏิบัติ และ 3) การศึกษาจากข้อมูลเอกสารที่เกี่ยวข้อง เช่น สมุดบันทึกสะท้อนคิดของนักศึกษา เมื่อได้ข้อมูลที่อิ่มตัวแล้ว วิเคราะห์เนื้อหาจำแนกเป็นประเด็นตามสิ่งที่ค้นพบ และใช้วิธีการตรวจสอบสามเส้าเพื่อตรวจสอบและแปลความข้อมูล ผลการวิจัย พบว่า ผู้ให้ข้อมูลส่วนใหญ่รับรู้และมีทัศนคติเชิงบวกต่อ “การเรียนรู้เชิงรุก” เทคนิคและวิธีการสอนที่ได้ปรับใช้ แบ่งเป็น 3 กลุ่ม คือ1) ใช้ง่าย 2) ปานกลาง และ 3) มีเอกลักษณ์เฉพาะตัวสิ่งสนับสนุนหรือปัญหาอุปสรรค มีหลายปัจจัย ได้แก่ ด้านตัวของผู้สอน ตัวของผู้เรียน ชุมชนหรือพื้นที่แหล่งฝึก และระยะเวลาที่จำกัดในการฝึกปฏิบัติ ผู้สอนส่วนใหญ่ได้ใช้เทคนิคและวิธีการสอนที่หลากหลาย และปรับใช้ได้อย่างเหมาะสมกับสถานการณ์จริง แม้จะเป็นประสบการณ์ “ใหม่” ของผู้สอน ต่อการใช้แนวคิด “การเรียนรู้เชิงรุก” แต่ทัศนคติที่ดีช่วยให้สามารถประยุกต์ใช้เทคนิคและวิธีการสอนในรายวิชาปฎิบัติการพยาบาลได้ค่อนข้างดี จึงควรสนับสนุนให้มีการแลกเปลี่ยนเรียนรู้เทคนิคและวิธีการสอน รวมทั้งการแก้ไขปัญหาอุปสรรคระหว่างผู้สอนด้วยกัน เพื่อประโยชน์สูงสุดต่อผู้เรียน และชุมชนหรือพื้นที่แหล่งฝึกต่อไป คำสำคัญ : การรับรู้ทัศนคติและประสบการณ์ การเรียนรู้เชิงรุก เทคนิคและวิธีการสอน การปฏิบัติการพยาบาลอนามัยชุมชน ABSTRACT Very few research studies in nursing education have been investigated beneficial teaching/learning effects of “active learning” approach upon lecturers. This preliminary study was conducted with the aims to explore 1) lecturer’s perceived attitudes of the “novice” upon the “active learning” approach, 2) their perceived experiences in utilizing relevant “teaching techniques”, upon a community health nursing practicum, and 3) supporting/inhibiting factors against this approach. Key informants were full time lecturers in department of Public Health Nursing, willing to participate, and have supervised undergraduate nursing students in the field within the past two calendar years. Several qualitative research techniques were used in gathering information: in-depth interview by using semi-guideline questions to ask six lecturers’ responsesindividually; participatory observation while jointly supervised students; and secondary documents collection, such as, student’s self-reflective diary, etc. Content analysis was used to analyze the saturated data, revealing emerging themes. “Triangulation” techniques were used to confirm data interpretation. Most participants perceived positive attitudes towards this approach. All supported its’ necessity and appropriateness in teaching-learning activities. Most utilized various “active learning” teaching techniques, and adapted properly to fit well with actual situations. Three groups of teaching techniques were categorized: the “easy” usage, the “modest” use, and the “unique” using. Four dimensions of supporting/inhibiting factors were found: lecturers, students, community settings, and time constraints. Positive attitudes could enhance utilizing this approach successfully. Learning-teaching experiences should be shared among faculty members. Solving the obstacles should be supported in order to obtain utmost beneficial effects for nursing students and communities as well. Keywords : Perceived Attitudes and Experiences, Active Learning, Teaching Techniques, Community Health Nursing Practicum